Clinical Practice and Effectiveness Analysis of the Management of Corona Virus Disease 2019 Infected at Shanghai Fangcang Shelter Hospital: A Descriptive Study - Zhu J; Zhu GP; Weng YM; Zhang Y; Li BX (Dove Medical Press, 2023)
Jian Zhu,1,* Guang-Ping Zhu,2,* Yan-Ming Weng,3,* Yong Zhang,4 Bi-Xi Li5 1Department of Thoracic Cardiovascular Surgery, General Hospital of Central Theater Command of the People's Liberation Army, Wuhan, People's Republic of China; 2Department of Endocrinology, General Hospital of Central Theater Command of the People's Liberation Army, Wuhan, People's Republic of China; 3Department of Stomatology, General Hospital of Central Theater Command of the People's Liberation Army, Wuhan, People's Republic of China; 4Department of Integrative Medicine, General Hospital of Central Theater Command of the People's Liberation Army, Wuhan, People's Republic of China; 5Department of Anesthesiology, General Hospital of Central Theater Command of the People's Liberation Army, Wuhan, Hubei Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Yong Zhang; Bi-Xi Li, Tel +86-13986107360 ; +86-13397192089, Email zbzqzyyzy@163.com; Bxlee@sohu.comBackground: The Fangcang shelter hospital has gradually become the primary management mode in China's fight against this Corona Virus Disease 2019 (COVID-19) in 2020. In early 2022, the Fangcang shelter hospital management model was successfully applied to the new outbreak of COVID-19 in Shanghai also. Although Fangcang shelter hospitals are no longer the prevailing mode of prevention of COVID-19, the management experience of Shanghai makeshift hospitals is worthy of reference for public health.Methods: The authors conducted a descriptive statistical analysis of Hall 6-2 of the Shanghai National Convention and Exhibition Center Fangcang shelter hospital. The whole hall of the Fangcang shelter hospital was managed by the one hospital, and the inclusion of third-party management personnel alleviated the shortage of medical personnel human resources. Through practice, a new procedure for treating batch infected people was introduced.Results: By optimizing ward management, 72 on-duty doctors, 360 on-duty nurses, 3 sense-control administrators, and 15 administrators cured 18,574 infected people in 40 days, and created a record of a doctor managing 700 infected people without compromising the quality of treatment. There have been no deaths and no complaints from the infected people located in Hall 6-2 of the Shanghai National Convention and Exhibition Center Fangcang shelter hospital.Conclusion: Compared with previous data, the new management mode of Fangcang shelter hospitals provides a reference for the management of the new infectious diseases for public health.Keywords: COVID-19, Omicron variant, Fangcang shelter hospital, management, Shanghai's experience